The Improvement of Etrepreneurial Interest Through Entrepreneurship Education, Entrepreneurship Sprit and Entrepreneurship Motivation - Sukirman, -; Afifi, Zaenal (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2021)
This study aimed to analyze the impact of entrepreneurship education, entrepreneurship spirit and entrepreneurship motivation on the entrepreneurial interest of Muria Kudus University students. The population consisted of 865 students who enrolled a compulsory students entrepreneurial skills training. The sample was 125 students. Data analysis was done using AMOS for (SEM) Structural Equation Modelling. The results showed thatentrepreneurship education had a positive and significant impact on entrepreneurial interest. Entrepreneurship spirit had a positive and significant impact on entrepreneurial interest. Entrepreneurship education had a positive and significant impact on entrepreneurship motivation. Entrepreneurihip spirit had a positive and significant impact on entrepreneurship motivation. Entrepreneurship motivation had a positive and significant impact on entrepreneurial interest.Keywords: Entrepreneurship Education, Entrepreneurship Spirit, Entrepreneurship Motivation, and Entrepreneurial Interest